A Survey of Clinical Opinions and Preferences on the Non-surgical Management of Intermittent Exotropia in China. Issue 4 (2nd October 2021) - Wu, Yidong; Peng, Tingting; Zhou, Jinjing; Xu, Meiping; Gao, Yi; Zhou, Jiawei; Hou, Fang; Yu, Xinping
ABSTRACT: Purpose: This study reports clinical opinions and preferences on the non-surgical management of intermittent exotropia (IXT) among practitioners in China. Methods: An online survey was developed and distributed through professional bodies. The study was conducted from July 25 th to August 3 rd, 2019. A total of 300 ophthalmologists and 188 optometrists responded. Results: Of 488 participants, 257 (53%) considered fusion defects as the main cause of IXT, and 299 (61%) took IXT as a progressive disorder. Two hundred and seventy-one (56%) participants considered orthoptic exercises as the most effective non-surgical intervention for IXT. Likewise, 245 (50%) participants reported that orthoptic exercises were their most frequent non-surgical option, followed by observation (178, 37%). There are discrepancies between ophthalmologists and optometrists. A greater proportion of ophthalmologists (201, 67%) shared the view that IXT worsens over time (98, 52%) ( p = .001). Additionally, ophthalmologists (121, 40%) tended to prefer observation compared with optometrists (57, 30%) ( p = .021). Conclusions: This study shows that there is no general consensus on the non-surgical management of IXT in China. Given the lack of robust evidence, the findings from this study highlight the need for future randomized clinical trials to validate the effectiveness of non-surgical interventions, orthoptic exercises in particular, and to establish treatment guidelines accordingly.